Perceived organizational support and social support as predictors on turnover intention among offshore oil and gas workers in Malaysia - Rubenesvaran Rau, Home Narayanan; Yaw, Kah Yipp; Yew, Jin (2019)
Oil and gas industry throughout nations are reported to have high employee turnover including Malaysia, third largest exporter Liquefied Natural Gas exporter in the industry. The current study aims to examine the relationship between perceived organizational support, perceived social support and turnover intention among offshore oil and gas workers in Malaysia. Quantitative, cross-sectional research design was used for the correlation study. One hundred forty six (n=146) offshore oil and gas workers were recruited via snowball sampling. Paper and pen and online survey method (Qualtrics) were used for data collection. The variables of the study were measured by Multidimensional Scale of Perceived Social Support (MSPSS), Survey of Perceived Organizational Support (SPOS) and Turnover Intention Scale 15-Item version (TIS-15). Results indicate that individuals with higher score of perceived organizational support and perceived social support will have lower turnover intention. In addition, multiple regression analysis shows that perceived organizational support is stronger predictor for turnover intention compared to perceived social support. Findings from this study will be asset for future studies as well providing input to oil and gas organizations for their employee retention plans.